In Vitro Evaluation of Nanoemulsion of Gotu Kola Leaves (Centella Asiatica Urb.) as an Alternative Treatment for Tuberculosis: Evaluation of Nanoemulsion of Centella Asiatica Urb. as Tuberculosis Treatment - Ainurofiq, Ahmad; Shofi, Faazatus; Ningsih, Silvia Ratna; Haifani, Ashrifathia; Herawardhani, Nadia (Iranian Journal of Pharmaceutical Sciences, 2026)
Gotu kola leaves (Centella asiatica Urb.) contain asiaticoside compounds that have been demonstrated to possess bactericidal properties against Mycobacterium tuberculosis (M. tuberculosis), as evidenced by inhibition tests. Several studies have reported that M. tuberculosis has developed resistance to tuberculosis (TB) drugs. The nanoemulsion delivery system represents an innovative therapeutic approach for TB patients, demonstrating significant promise in the diagnosis, treatment, and prevention of infectious diseases such as TB. This study aims to optimize and formulate the manufacture of a gotu kola leaf extract nanoemulsion as an alternative TB treatment. Maceration was employed to obtain a gotu kola leaf extract, yielding 34.7%. Thin-layer chromatography (TLC) analysis revealed a single spot, confirming the presence of asiaticoside. A gotu kola leaf nanoemulsion was developed using the Box-Behnken Design method, incorporating variations in gotu kola leaf extract loading, tween 80, and sonication time. The optimal formula was determined based on particle size parameters, particle size distribution, entrapment efficiency (EE), and extract loading (EL) using Stat-Ease® Design-Expert 360 software. The writing has been corrected. The optimal formula exhibited a particle size of 154.715 nm, a particle size distribution of 0.246, an EE of 92.512%, and an EL of 98.298 mg/g. In vitro testing demonstrated the antibacterial potential of the optimum formula, achieving a 56.2% antibacterial effect. In contrast, the positive control rifampicin showed an 89.1% antibacterial effect.